AND 2021
DOI: 10.20517/and.2021.04
|View full text |Cite
|
Sign up to set email alerts
|

Naive BM-derived stem cells (Neuro-Cells) may modify acute and chronic neurodegenerative disorders by modulating macrophage behaviors

Abstract: BW. Naive BM-derived stem cells (Neuro-Cells) may modify acute and chronic neurodegenerative disorders by modulating macrophage behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Owing to their self-renewing and pluripotent properties, neural stem cells (NSCs) are potentially transplantable cells [186]. However, due to the inflammatory environment's toxic effect, most transplanted NSCs transformed into glial cells rather than neurons, and only a few transplanted NSCs survived [187,188]. Therefore, addressing the inflammatory host brain environment improves the abnormal behaviors in PD rats.…”
Section: Nurr1 As a Potential Neuroprotective And Anti-inflammatory T...mentioning
confidence: 99%
“…Owing to their self-renewing and pluripotent properties, neural stem cells (NSCs) are potentially transplantable cells [186]. However, due to the inflammatory environment's toxic effect, most transplanted NSCs transformed into glial cells rather than neurons, and only a few transplanted NSCs survived [187,188]. Therefore, addressing the inflammatory host brain environment improves the abnormal behaviors in PD rats.…”
Section: Nurr1 As a Potential Neuroprotective And Anti-inflammatory T...mentioning
confidence: 99%
“…Other study found that increased microglia that one of the strongest genetic risk factors for Alzheimer's disease, cannot metabolize lipids normally [39]. Increased Iba-1 become activated following exposure to pathogen-associated molecular patterns and/or endogenous damage-associated molecular patterns and removal of the immunesuppressive signals [40]. Activated microglia can acquire different phenotypes depending on cues in its surrounding environment [41].…”
Section: Ionized Calcium Binding Adaptor Molecule 1 (Iba1)mentioning
confidence: 99%
“…Microglia account for approximately 10% of cells in the CNS, which usually exist in a resting state and contribute to modulating the strength of synaptic transmissions and sculpting neuronal synapses ( Colonna and Butovsky, 2017 ). Microglia appear to be heterogeneous with diverse functional phenotypes that range from pro-inflammatory M1 phenotypes to immunosuppressive M2 phenotypes ( Tang and Le, 2016 ; Zhang et al, 2017 ; Wolters et al, 2021 ). Once sensing damage signals or toxic aggregated proteins inside or outside the cell, microglia will switch from resting to active ( Zhong et al, 2018 ; Dong et al, 2020 ).…”
Section: Extracellular Vesicles In Glia-neuron Communicationmentioning
confidence: 99%